2010
DOI: 10.1038/hr.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clonidine in patients with essential hypertension with neurovascular contact of the rostral ventrolateral medulla

Abstract: The rostral ventrolateral medulla (RVLM) is an important center for regulation of sympathetic nerve activity. Several clinical studies have suggested an association between neurovascular contact (NVC) of RVLM and essential hypertension. Microvascular decompression (MVD) of RVLM decreases blood pressure (BP) in hypertensive patients with NVC of this region. Therefore, MVD could be a useful therapeutic strategy to reduce BP in these patients. However, as MVD is an invasive procedure, it is worthy to seek useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In a recent Japanese study it has been reported, similar to many previous studies, that prevalence of NVPC of the RVLM was significantly higher in the group of patients with primary HT (35%) than in the normotensive group (13%) (p<0.05) [3,4,14,15,16,17,18]. A recent study using high-resolution MRI scans with 1 mm slices showed that the frequency of NVPC of the RVLM was clearly and significantly higher in patients with primary HT (73.5%) than in patients with secondary HT (12.5%) [19].…”
Section: Discussionsupporting
confidence: 70%
“…In a recent Japanese study it has been reported, similar to many previous studies, that prevalence of NVPC of the RVLM was significantly higher in the group of patients with primary HT (35%) than in the normotensive group (13%) (p<0.05) [3,4,14,15,16,17,18]. A recent study using high-resolution MRI scans with 1 mm slices showed that the frequency of NVPC of the RVLM was clearly and significantly higher in patients with primary HT (73.5%) than in patients with secondary HT (12.5%) [19].…”
Section: Discussionsupporting
confidence: 70%
“…The anatomy and imaging data of patients with hypertension also showed that the left side of the ventrolateral medulla oblongata and vagus nerve REZ offending vessels are more than the right. 21 22 However, we found that the change in BP between 3 days before and 7 days and 6 months after MVD was not significantly associated with laterality of pathology, which refutes the idea that only the left side is involved in BP regulation. This supports the opinion proposed by Sindou et al, 4 which indicates that both the left and right ventrolateral medulla and vagus nerve REZ are involved in BP regulation.…”
Section: Discussionmentioning
confidence: 66%
“…The effect of these drugs on the course of MS may vary depending on their selectivity toward and ARs. For example, the 2 AR agonist, Clonidine, reduces NE plasma levels in hypertensive patients [68]. Since it is a centrally-acting agent, Clonidine-induced activation of CNS 2 ARs may promote CNS neurodegenerative processes through the activation of MAP kinases [9,10].…”
Section: Antihypertensive Agents In Msmentioning
confidence: 99%